PERTUMBUHAN DAN KELULUSHIDUPAN IKAN JUARO (PANGASIUS POLYURANODON, BLKR) DENGAN PEMBERIAN JENIS PAKAN BERBEDA PADA SISTEM RESIRKULASI - Anggi Sugito; Niken Ayu Pamukas; Rusliadi Rusliadi (Berkala Perikanan Terubuk, 2017)
This research was conducted on April 20th to June 3rd, 2017 in the Hatchery Hall TIU (Technical Implementation Unit) of Aquaculture Major Marine and Fishery Faculty, Riau University, Riau Province. The aim of the study was to know the effect of different feeding type toward the growth performance and survival rate of Pangasius polyuranodon, Blkr. The method was using the experimental method with four treatment levels and three replication, the treatments were Tubifex sp. (P1), feed with Tubifex sp. + Pelet + Tubifex sp. (P2), feed with Pelet + Tubifex sp. + Pelet (P3), and feed with only Pelet (P4). The data were analyzed by using ANOVA (P <0,05). The material was 60 fries of Pangasius polyuranodon which were rearing in the 12 aerated aquariums that covered with black plastic from all side. The filter materials were zeolite stone and spons.   The results were shown that the feed type using Tubifex sp. (P1) gave the best result with absolute weight growth 4,19 gram, specific growth rate 1,10%, absolute length growth 2,79 cm, and the survival rate was 80%. The water quality measurements were temperature was around 27-30oC, dissolved oxygen (DO) was around 5,01-6,14 mg/L, pH 6,4-7,4 and Ammonia was around 0,001-0,056 mg/L.